MENGQADHA SHALAT DALAM PERSPEKTIF FIQH ISLAM - Kholid Saifulloh (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2020)
Prayer is the second pillar of Islam after two sentences of shahada. Prayer has a very important position for Islam, so the Prophet sallallaahu'alaihiWasallam likened it like a pillar to a building, so that a building will not be able to stand firmly without a supporting pillar. Likewise a person's Islam cannot be established without establishing prayer. However, sometimes intentionally or not, a Muslim leaves the prayer until out of time. By remembering the importance of prayer, can the missed prayer be replaced (qada’)? In this paper, the author presents a discussion of three things related to qada’ prayer: the arguments about qada’ prayer, the law of qada’ prayer and various types of prayers that can be replaced (qada’), as well as the requirements that must be fulfilled in qada’ prayer.